2018
DOI: 10.3892/ol.2018.8492
|View full text |Cite
|
Sign up to set email alerts
|

Long non‑coding RNA NNT‑AS1 contributes to cell proliferation, metastasis and apoptosis in human ovarian cancer

Abstract: Ovarian cancer is a markedly heterogeneous malignancy characterized by various histological subtypes. Molecular biomarkers have been indicated to serve significant functions in the early diagnosis and treatment of early-stage ovarian cancer. However, the detailed mechanism underlying the tumorigenesis of ovarian cancer remains unclear. The present study aimed to identify a novel long non-coding RNA in patients with ovarian cancer. Nicotinamide nucleotide transhydrogenase-antisense 1 (NNT-AS1) was markedly down… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 22 publications
4
21
0
Order By: Relevance
“…It is worth noting that NNT-AS1 was down-regulated in studies [34,[37][38][39] on ovarian cancer, triple-negative breast cancer, and gastric cancer, which is inconsistent with the results of the others [32,33,35,36]. These differences need to be further verified in large-scale experiments, and the connection between NNT-AS1 and sex hormones and sex hormone receptors deserves more in-depth exploration.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…It is worth noting that NNT-AS1 was down-regulated in studies [34,[37][38][39] on ovarian cancer, triple-negative breast cancer, and gastric cancer, which is inconsistent with the results of the others [32,33,35,36]. These differences need to be further verified in large-scale experiments, and the connection between NNT-AS1 and sex hormones and sex hormone receptors deserves more in-depth exploration.…”
Section: Discussionmentioning
confidence: 86%
“…A recent bioinformatics study based on Gene Expression Omnibus (GEO) data analyzed the expression of lncRNA in triple-negative breast cancer (including ER-negative), in which NNT-AS1 was also found to be down-regulated [38]. In addition, in a study on ovarian cancer, the low level of NNT-AS1 was confirmed as well [39].…”
Section: The Aberrant Expression Of Nnt-as1 In Cancermentioning
confidence: 99%
“…The lncrna nicotinamide nucleotide transhydrogenase-antisense rna1 (nnT-aS1), located at 5p12 with 3 exons, is a newly identified lncRNA (7). NNT-AS1 has been reported to be involved in the progression of lung, ovarian, breast and gastric cancer, as well as osteosarcoma (8)(9)(10)(11)(12)(13). it has also been reported that nnT-aS1 expression was increased in Gc tissues and cell lines (14); however, the molecular mechanism underlying nnT-aS1 in Gc is not completely understood and requires further investigation.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with adjacent noncancerous tissue and normal cell, upregulated NNT-AS1 expression was identi ed in most cancer tissues or cell lines and therefore indicated poor survival outcome, such as osteosarcoma [27], breast cancer [19], cervical cancer [26], gastric cancer [28], hepatocellular carcinoma [18], colorectal cancer [21], and non-small cell lung cancer (NSCLC) [2]. On the contrary, another study performed by Huang et al, claimed that NNT-AS1 was markedly downregulated in patients with ovarian cancer and ovarian cell lines [29]. However, results from above-mentioned studies should be interpreted with caution because of the limited sample size and discrete outcomes.…”
Section: Discussionmentioning
confidence: 99%